헬리콥터 부모양육태도가 대학생의 우울에 미치는 영향: 주장성의 매개효과 - 김가연(Ga Yeon Kim); 박주희(Ju Hee Park) (Korean Journal of child studies, 2019)
Objectives: This study aimed to investigate the mediating effect of assertiveness in the relationship between perceived helicopter parenting and depression among university students. Methods: The participants of this study were 609 students (272 males and 337 females) who were enrolled in 25 universities located in Seoul and Gyung-gi province in Korea. The research variables were measured using the Center for Epidemiological Studies-Depression Scale (CES-D), Helicopter Parenting Scale (HPS), and Rathus Assertiveness Schedule (RAS). In order to examine the general tendency of the study variables, descriptive statistics and Pearson’s correlation coefficients were calculated. Path analysis was also used to examine the mediating model. Results: The results of this study were as follows; First, the level of perceived helicopter parenting increased the level of depression and decreased that of assertiveness in students. In addition, students’ level of assertiveness had a significant negative influence on their level of depression. Second, the level of assertiveness partially mediated the effect of perceived helicopter parenting on depression. Conclusion: In conclusion, the higher the level of perceived helicopter parenting, the lower the level of students’ assertiveness and, subsequently, the higher their level of depression. These results suggested that reducing the level of helicopter parenting and encouraging assertiveness among university students would play an important role in reducing their depression. KCI Citation Count: 12